Imperatives for legal education research : then, now and tomorrow - Steel, Alex; Golder, Ben; Vines, Prue, 1956-; Nehme, Marina (Emerging legal education., 2020)
"In the last few decades university teaching has been recognised as an activity which can be studied and improved through educational scholarship. In some disciplines this is now well established. It remains emergent in legal education. The field is rich with questions to be answered, issues to be raised. This book provides the first overall review of legal education scholarship. The chapters outline the history of legal education research and provide a detailed analysis of the trends in areas of publication. Beyond this, the book suggests a typology for further conceptualising the field and a series of suggested paths for future research. The book originated from the 2017 UNSW conference "Research in Legal Education: State of the Art?" It features internationally respected authors who bring their perspectives on how legal education - as a field of research - should be conceptualised. The collection is arranged into three themes. First, a historical view is taken of the emergence of legal education scholarship and its roots that predate modern educational theory. Secondly, the book provides overviews of the extant field of publications, highlighting areas of interest and neglect, and delineating the trends in current publication. Thirdly, the book provides a set of suggested typologies for describing legal education research and a series of essays for future directions which both critique current approaches and provide inspiration for future directions. The State of Legal Education Research represents an authoritative introduction to the field, a set of conceptual tools with which to describe it, and inspiration for researchers to expand and grow research into legal education"--